A computer model of drafting effects on collective behavior in elite 10,000-m Runners - Trenchard, H.; Renfree, A.; Peters, D. M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Drafting in cycling influences collective behavior of pelotons. Although evidence for collective behavior in competitive running events exists, it is not clear if this results from energetic savings conferred by drafting. This study modeled the effects of drafting on behavior in elite 10,000-m runners.